Ovarian Sex Cord-Stromal Tumors in Patients With Probable or Confirmed Germline DICER1 Mutations. (May 2015) - Oost, E. Ebo; Charles, Adrian; Choong, Catherine S.; Leung, Yee C.; Salfinger, Stuart; Sonnendecker, Hein; Tan, Jason; Townshend, Sharron; Witkowski, Leora; Foulkes, William D.; Stewart, Colin J. R.
Abstract : The DICER1 gene encodes an endoribonuclease involved in the production of mature microRNAs which regulates gene expression through several mechanisms. Recent studies have demonstrated somatic mutations in DICER1 in approximately 60% of ovarian Sertoli-Leydig cell tumors. Furthermore, patients with germline mutations in DICER1 are predisposed to developing a range of rare neoplasms including ovarian sex cord-stromal tumors most of which have been classified as Sertoli-Leydig cell tumor. However, the histologic features of these tumors have not been reported in detail. We describe the morphologic and immunophenotypic findings of 4 sex cord-stromal tumors arising in patients with proven or likely germline DICER1 mutations including 3 individuals from 1 family. Three tumors showed similar appearances characterized by marked architectural and cytologic heterogeneity including sertoliform, juvenile granulosa cell tumor-like, and unclassifiable elements. The remaining case mainly showed heterologous mucinous epithelial and neuroendocrine differentiation with only a minor intermediate-grade Sertoli cell component. This tumor and one of the 3 former cases arose in related patients with identical germline DICER1 mutations indicating that additional factors influence tumor morphology. All tumors were positive for steroidogenic factor-1 and FOXL2 on immunohistochemical analysis, whereas there was more variable expression of inhibin, calretinin, CD56, CD99, and hormone receptors. The present small series suggests that some ovarian Sertoli-Leydig cell tumor associated with germline DICER1 mutations may show distinctive histologic features in particular admixed Sertoli cell and juvenile granulosa cell tumor-like features. Larger studies are required to establish whether heterologous elements are also a more common feature of these tumors.